The effect of financial literacy and digital payment technology on financial vulnerability: A crucial investigation - Ajeng Wahyu Azizah; dhyah setyorini (Kompartemen: Jurnal Ilmiah Akuntansi)
This study examines the effect of (1) financial literacy on student financial vulnerability and (2) digital payment technology on student financial vulnerability. This research approach uses a quantitative approach. The method used is the survey method. The population in this study were accounting students of Yogyakarta State University (UNY) batch 2017 - 2023, and the sampling method used convenience sampling. The research sample was obtained from 86 students from the 2017-2023 class and divided into proportions. Hypothesis testing using multiple linear regression analysis. The results of this study indicate that (1) financial literacy does not affect financial vulnerability; (2) digital payment technology has a significant positive effect on financial vulnerability.